A study on gender discrimination in the workplace in Malaysia / Siti Nurul Dyana Pringadi, Fahirah Norjihan Mokhtar and Siti Manisah Che Ismail - Pringadi, Siti Nurul Dyana; Mokhtar, Fahirah Norjihan; Siti Manisah, Che Ismail (2006)
Gender discrimination means treating an individual differently on the basis of their sex. Nowadays, the issue of gender discrimination had caught the attention of Malaysian ever since the issue is intensively debated in the Parliament. Recently, during the celebration of International Women Day, the Deputy Prime Minister had announced that law and policies that do not promote equality for women should be revised. This on-going issue pertaining to gender discrimination, which had been raised by various non-government organisation, scholars and feminist for decades had finally been answered through the effort from the government in achieving gender equality. Besides, the government is under the commitment to create a 'First-Class Mentality' to move boldly to mediocrity to excellence and meritocracy regardless of gender, ethnicity, or even nationality. The purpose of this research paper is to investigate awareness of legal rights and responsibilities in respect of gender discrimination. Although there are many efforts from the both sides, government and non-government organisations, the degree of the awareness among women in Malaysia pertaining their rights under labour law are still relatively low. Some of them do not even know about the existence of these rights. Good law seems to have less value when people are reluctant to appreciate it. Women's right under employment should be recognized widely in administration not even to people at large but also to women themselves. This research paper also seeks to answer what is covered by the law regarding gender discrimination. It is significant to know the access to justice for ensuring that these women are not being simply discriminated.